Modelling the Demand for Fresh Meat in Malaysia - Nordiana Marjan Rusli; Assis Kamu (2018)
Malaysia is one of the most developing countries in Asia. Hence, there have been significant changes in Malaysians’ food preference. These changes in consumption pattern have some impact on agri food industry in Malaysia. One of the changes is the preference towards fresh meat such as beef, poultry, mutton and other meat. This research will be focusing on demand of poultry meat in Malaysia. Data from Household Expenditure Survey 2014 will be used in order to build a statistical model in estimating the demand for poultry meat. The development of the demand model will be based on best subsets regression approach.